Reactions in the solid state - Brown, Michael Ewart (Rhodes University, Faculty of Science, Department of Chemistry, 2006)
I have chosen the title for this thesis, "Reactions in the Solid State", for two reasons: Firstly, it is broad enough to cover all of my areas of research, which have been: "¢ Effects of irradiation on solids (PhD topic) "¢ Silver refining (while at the Chamber of Mines) "¢ Kinetics of decomposition of solids (with Dr A.K. Galwey and various others) "¢ Techniques of thermal analysis "¢ Pyrotechnic delay systems (with support from AECI Explosives) "¢ Thermal and photostability of drugs (with Prof B.D. Glass) and, secondly, it was the title of the very successful book co-authored by Drs Andrew Galwey, David Dollimore and me. A large part of my research has been involved in the writing and editing of books, so these are covered in a separate commentary, while commentary on the more than 100 papers to which I have contributed forms the main part of this compilation. It is hoped that the electronic format will enable ready access of to all aspects of my research, including electronic versions of the original papers. The reader will need a copy of Adobe Acrobat Reader to access these.
Keywords: Solid state chemistry; Thermal analysis; Chemistry, Analytic